Safety and efficacy of brivaracetam in children epilepsy: a systematic review and meta-analysis - Song, Ting; Feng, Lingjun; Xia, Yulei; Pang, Meng; Geng, Jianhong; Zhang, Xiaojun; Wang, Yanqiang (Frontiers in Neurology, 2023)
Background: Epilepsy is one of the most common neurological diseases, affecting people of any age. Although the treatments of epilepsy are more and more diverse, the uncertainty regarding efficacy and adverse events still exists, especially in the control of childhood epilepsy. Methods: We performed a systematic review and meta- analysis following the Cochrane Handbook and preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Four databases including PubMed, Embase, Web of Science and Cochrane library were searched. Studies reporting the use of brivaracetam monotherapy or adjuvant therapy in children (aged ≤ 18 years) were eligible for inclusion. Each stage of the review was conducted by two authors independently. Random-effects models were used to combine effect sizes for the estimation of efficacy and safety. Results: A total of 1884 articles were retrieved, and finally 9 articles were included, enrolling 503 children with epilepsy. The retention rate of BRV treatment was 78% (95% CI: 0.64-0.91), the responder rate (reduction of seizure frequency ≥ 50%) was 35% (95% CI: 0.24-0.47), the freedom seizure rate (no seizure) was 18% (95% CI: 0.10-0.25), and the incidence rate of any treatment-emergent adverse events (TEAE) was 39% (95% CI: 0.09-0.68). The most common TEAE was somnolence, which had an incidence rate of 9% (95% CI: 0.07-0.12). And the incidence rate of mental or behavioral disorders was 12% (0.06-0.17). Conclusions: Our systematic review and meta-analysis showed that BRV was seemed to be safe and effective in the treatment of childhood epilepsy.